ANXIETY AS REFLECTED IN FRIEDRICH DUERRENMATT'S THE VISIT: A PSYCHOANALYTIC APPROACH - PURNOMO , YULI BRATYASTUTI (2006)
The problem of the study is to reveal how major character reflects his anxiety. The aim of this study is to analyze Friedrich Duerrenmatt's The Visit based on psychoanalytic approach. In so doing, the study focuses on the character, namely Anton Schiil. The benefit of the study is to give additional information whi ch can be used by the other literature researcher who is interested in analyzing this play. The study uses two data sources, namely primary and secondary data source. The primary data source is the manuscript of the play itself, while the secondary data are taken from some information needed. The method of data collection is qualitative method. Based on the analysis, the outcome of this study shows that the problem of major character encounters is the conflict of her mental condition. Then, it develops to become anxiety and influences her to do some ways to escape from it. Finally, the change of personality makes him suffer and dead in the end.